Conformity and Cyber-Aggression Behavior in Adolescent Social Media Users - Sau, Lidia Yana R. L.; Benu, Juliana Marlin Y.; Artati, Mardiana (Journal of Health and Behavioral Science, 2025)
This study aims to examine the relationship between conformity and cyber-aggression behavior among adolescent social media users in Kupang City. A quantitative correlational approach was employed, involving 360 adolescents aged 12 to 22 years who are active social media users. The instruments used were conformity and cyber-aggression scales. Data analysis using Spearman’s Rho test revealed a significant positive correlation between conformity and cyber-aggression behavior, with a correlation coefficient of 0.163 and a significance value of p = 0.002 (p < 0.05). These findings indicate that the higher the level of conformity among adolescents, the greater their tendency to engage in aggressive behavior on social media. This result is important as a basis for developing strategies to prevent online aggressive behavior among adolescents.